PENGARUH LATIHAN PLYOMETRICS BOX JUMP TERHADAP POWER OTOT TUNGKAI PADA ATLET BULU TANGKIS PB. EXIST INVICTUS BADMINTON TULANG BAWANG LAMPUNG DIMASA NEW NORMAL - Abrar Karim Sastra Wardana; Ni Putu Nita Wijayanti; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstark: The problem in this research is that the foot steps are not adjusted to jump, and the vertical jump is not maximal when hitting. The form of this research is (one group pretest-posttest design) with PB badminton athletes. Exist Inveictus Tulang Bawang. The data in this research were the entire population of 10 people. The instrument used in this research is to use a vertical jump test, which aims to determine the effect of box jump plyometrics exercise. Based on the analysis of the normality test on the independent variable (X) it produces LoMax of 0.171 and Ltable of 0.258, meaning LoMax < Ltable. while the dependent variable (Y) produces LoMax of 0.167 and Ltable of 0.258. This means that LoMax < L The data table is normally distributed. In testing the t distribution hypothesis, it can be concluded that between the x variable and y variable, the value of t = 3.250 is obtained, then tcount > ttable, namely (3.250) > (1.833), then Ha is accepted, in other words there is an effect of plyometrics box jump exercise on leg muscle power in PB badminton athlete. Exist Invictus Badminton Tulang Bawang Lampung in the new normal era.Key Words: Plyometrics Box Jump Exercise, Power Muscle, Badminton